Politeness Strategies in a Speech by Jordan B. Peterson about "How to be Articulate" - Pirdehghan, Ali (Journal of Language and Literature, 2024)
Politeness is a concept in the area of pragmatics and conversational analysis in which the speaker considers several factors to be polite, including their relationship with the hearer, their age, the power they have over the hearer, the importance of their utterances, etc. Speeches from prominent figures provide rich sources of analysis on politeness, a vital concept in everyday communication. This study examines different realizations of politeness strategies. The researcher used Brown and Levinson's model (1987), categorizing the strategies into four main realizations (Bald on-record, positive politeness, negative politeness, and off-record). The data source has been a 15-minute video clip from Jordan B. Peterson – a prominent Canadian psychologist and author – about being articulate, for which a qualitative method was used. During the data analysis, first, the author watched the video clip to get the gist, then wrote its transcription to look for the types of strategies used by the speaker. The transcription was then re-evaluated by two teachers in the field of English as a foreign language (EFL)to assure its inter-rater reliability. The results showed that the speaker employed the four types of politeness strategies during the speech, among which negative and positive politeness, together with their realizations – 'do not presume/assume' and 'raise/assert common ground were the most dominant. Further research on known figures, in different contexts and with larger data is imperative to ameliorate the pragmatics knowledge of both teachers and students and enhance their interactions.